October 7th Mass Casualty Attack in Israel: Injury Profiles of Hospitalized Casualties - Sharon Goldman, MPH; Ari M. Lipsky, MD; Irina Radimislensky, BSc; Adi Givon, BSc; Ofer Almog, MD; Avi Benov, MD; Israel Trauma Group; Eldad Katorza, MD, MSC, MBA; H. Bahouth; A. Bar; A. Braslavsky; D. Czeiger; et al. (Annals of Surgery Open)
Background:. On Saturday, October 7th, approximately 3000 Hamas-led terrorists infiltrated Israel’s southern border and attacked civilians and soldiers. Terrorists murdered close to 1200 people, abducted hundreds, and injured thousands. This surprise attack involved an unprecedented number of casualties. This article describes the injuries and outcomes of the hospitalized casualties. Methods:. Hospitalized trauma casualties with an injury date of October 7 to 8, 2023, and with ICD9 E-codes E979 and E990 through E999, were extracted from the Israel National Trauma Registry. Demographic, injury, and hospital resource-use data were analyzed. Results:. A total of 630 hospitalized casualties (277 civilians and 353 soldiers) suffered from gunshot wounds (90%), explosion-related wounds (19%), and multiple injury mechanisms (16%). The median age for civilians was 33 years (ages <1–88) and 21 years for soldiers. The most frequently injured body regions were lower (49%) and upper (42%) extremities, abdominal (28%), and thoracic (23%) injuries. Four hundred thirty-one (68%) patients underwent surgery, of which 240 within 12 hours. Over half of the severe and critical (Injury Severity Score 16+) casualties were discharged to a rehabilitation center. In-hospital mortality rate was 2.5%. Conclusion:. Israel’s hospitals faced many challenges following the mega mass casualty incident, including the absorption, diagnosis, treatment, and rehabilitation of a massive number of casualties. Hospitals needed to immediately repurpose to provide additional imaging equipment and operating rooms. Additionally, the huge demand for rehabilitation resources necessitated immediate reorganization and transformation of existing medical facilities to accommodate the many casualties requiring rehabilitation. The injury details and outcomes from this mega mass casualty incident provide important information for planning and preparedness at local, regional, and national levels.